The Reminiscences from Saadi’s Works in the Publicism and Epistolary of Ivan Bunin: The Source Studies Aspect of the Problem - Anton V. Bakuntsev (Studia Litterarum)
The article examines the problem of reminiscences from the works of the medieval Persian poet Saadi in the non-fiction texts of Ivan Bunin in the source studies aspect, using the principle of historicism and the method of comparative analysis. The objects of consideration were the letters and journalistic texts of the writer relating to 1910–1935, the subject was the images, sayings, maxims of Saadi reflected in them. The purpose of the study is to identify and analyze the sources of reminiscences from Saadi’s works, specifically their translated editions in Russian and the main European languages. The study found that, firstly, Bunin used as sources of Saadi’s texts not only the “classical” translations of books “Bustan” (1257) and “Gulistan” (1258), which appeared by the end of the 19th – beginning of the 20th centuries, but also related to one degree or another scientific, popular science and fiction literature by the poet’s creative work. Secondly, in Bunin’s epistolary and journalism, borrowings from Saadi’s works were subjected to quite significant creative processing.